Impact of Climate Conditions on the incidence of Ischemic Stroke in Sulaimani City - Karim, Bushra Qadir; Ghafur, Pshtiwan Gharib; Salih, Ahmed Omer (Sulaimani Journal for Humanities, 2022)
In previous studies, climate factors, such as temperature, barometric pressure were linked to the altered incidence of cerebrovascular disease, but findings have been inconsistent. The differences lie in whether it is positively related or negatively related. The aim of this was to assess the association between climate parameters and ischemic stroke onset. The study population was the patients admitted to the neurology unit of Shar hospital in Sulaimani city, Iraq. Climate data were collected over four years from January 1, 2015, to December 31, 2018. Data were analyzed using the SPSS program. Simple regression, multiple regression, coefficient of determination and correlation analyses were used to determine the impact of climate variables on the onset of ischemic stroke. The results showed a positive correlation between climate variables such as (maximum temperature, minimum temperature, average temperature, average wind speed) and incidence of ischemic stroke. However, average relative humidity and precipitation had a negative correlation with ischemic stroke occurrence. The number of patients has changed on seasonal levels. A total of 1255 patients were enrolled in this study. There were 156 (12.4%) patients aged 15 to 49 (72 males and 84 females) and 1099 (87.6%) patients over 50 years of age (560 males and 539 females). Impacts of variables on all groups and subgroups of patients were 60.3% (70.3% on male and 49.51% on female). The highest impact was 77.8% on the male group of 15 – 49 and the lowest was 40% on the female group of 15 – 49. Similarly, in seasonal scales maximum temperature had the highest positive relations in summer. Average wind speed had positive correlation in spring and autumn. Average relative humidity only in winter had a moderate positive correlation. Precipitation had a weak positive correlation in winter.
Keywords: Climate factors; Seasonality; Ischemic Stroke; Sulaimani City; Age and Gender